Epileptogenicity Maps of Intracerebral Fast Activities (60–100 Hz) at Seizure Onset in Epilepsy Surgery Candidates - Job, Anne-Sophie; David, Olivier; Minotti, Lorella; Bartolomei, Fabrice; Chabardès, Stephan; Kahane, Philippe (Frontiers in Neurology, 2019)
Fast activities (FA) at seizure onset have been increasingly described as a useful signature of the epileptogenic zone (EZ) in patients undergoing intracranial EEG recordings. Different computer-based signal analysis methods have thus been developed for objectively quantifying ictal FA. Whether these methods detect FA in all forms of focal epilepsies, whether they provide similar information than visual analysis (VA), and whether they might help for the surgical decision remain crucial issues. We thus conducted a retrospective study in 21 consecutive patients suffering from drug-resistant seizures studied by SEEG recordings. Ictal FA were quantified using the Epileptogenicity Maps (EM) method that we recently developed and which generates, by adopting a neuroimaging approach, statistical parametric maps of FA ranging from 60 to 100 Hz (FA60-100). Ictal FA were analyzed blindly using VA and EM, and the prognostic significance of removing areas exhibiting FA60-100 at seizure onset was evaluated. A significant ictal FA60-100 activation was found in all patients, and in 92.6% of all the 68 seizures recorded, whatever the epilepsy type. The overlap ratio (OR) between VA and EM was significantly better for defining the regions spared at seizure onset than those from which seizure arose (p<0.001), especially in temporal or temporal 'plus' epilepsies. EM and VA were much more discordant to define the EZ, with a mean number of electrode contacts involved at seizure onset significantly higher with EM than with VA (p=<0.0001). Seizure outcome correlated with the resection ratio for FA60-100, which was significantly higher in seizure-free (Engel's class Ia) than in non seizure-free patients (class Ic-IV) (p=0.048). The quantification of FA at seizure onset can bring information additional to clinical expertise that might contribute to define accurately the cortical region to be resected.